2000
DOI: 10.1086/318122
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Course of Oral Miltefosine for Treatment of Visceral Leishmaniasis

Abstract: A total of 54 Indian patients with visceral leishmaniasis were treated with oral miltefosine, 50 mg given twice daily, for 14 days (18 patients; group A), 21 days (18; group B), or 28 days (18; group C). Cure was achieved in 89% of group A, 100% of group B, and 100% of group C. Adverse reactions were self-limited and primarily mild. The 21-day miltefosine regimen combines high-level efficacy, convenient dosing, and a relatively short duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 12 publications
1
75
0
2
Order By: Relevance
“…Novas drogas de uso oral e vacinas para a LV vêm sendo desenvolvidas, com resultados animadores, mas, enquanto não dispomos destes avanços, devemos estar atentos para o diagnóstico da LV e utilizarmos as formas habituais de diagnóstico e tratamento, altamente eficientes no controle desta endemia 28,29 .…”
Section: Resultsunclassified
“…Novas drogas de uso oral e vacinas para a LV vêm sendo desenvolvidas, com resultados animadores, mas, enquanto não dispomos destes avanços, devemos estar atentos para o diagnóstico da LV e utilizarmos as formas habituais de diagnóstico e tratamento, altamente eficientes no controle desta endemia 28,29 .…”
Section: Resultsunclassified
“…Combinations of SSG and paromomycin have shown to be efficient and safe in India , Sudan (Seaman et al, 1993), and Kenya (Chunge et al, 1990) but paramomycin has yet to be registered for VL treatment and its future production and cost remain unclear. Other possible combinations could include in future trials conventional or liposomal amphotericin B as well as miltefosine, an oral drug showed to be very efficient in India when used alone for 4 weeks (Jha et al, 1999;Sundar et al, 2000b). Miltefosine was registered for the treatment of VL in India in 2002 and a phase IV trial will take place in India and Nepal in the coming year.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional antileishmanial therapies include the use of pentavalent antimonial compounds, amphotericin B, and pentamidine. More recently, miltefosine (hexadecylphosphocholine) has demonstrated efficacy against visceral leishmaniasis when administered orally (Sundar et al, 2000). However, current treatment strategies all suffer from drawbacks which include toxicity, developing resistance, administration by injection, and expense (Ouellette et al, 2004;Singh and Sivakumar, 2004).…”
Section: Introductionmentioning
confidence: 99%